Insect chaperones Hsp70 and Hsp90 cooperatively enhance toxicity of Bacillus thuringiensis Cry1A toxins and counteract insect resistance - García-Gomez, Blanca Ines; Sánchez, Tamara Alejandrina; Cano, Sayra Natalia; do Nascimento, Nathaly Alexandre; Bravo, Alejandra; Soberón, Mario (Frontiers in Immunology, 2023)
Bacillus thuringiensis (Bt) produces different insecticidal proteins effective for pest control. Among them, Cry insecticidal proteins have been used in transgenic plants for the control of insect pests. However, evolution of resistance by insects endangers this technology. Previous work showed that the lepidopteran insect Plutella xylostella PxHsp90 chaperone enhanced the toxicity of Bt Cry1A protoxins by protecting them from degradation by the larval gut proteases and by enhancing binding of the protoxin to its receptors present in larval midgut cells. In this work, we show that PxHsp70 chaperone also protects Cry1Ab protoxin from gut proteases degradation, enhancing Cry1Ab toxicity. We also show that both PxHsp70 and PxHsp90 chaperones act cooperatively, increasing toxicity and the binding of Cry1Ab439D mutant, affected in binding to midgut receptors, to cadherin receptor. Also, insect chaperones recovered toxicity of Cry1Ac protein to a Cry1Ac-highly resistant P. xylostella population, NO-QAGE, that has a disruptive mutation in an ABCC2 transporter linked to Cry1Ac resistance. These data show that Bt hijacked an important cellular function for enhancing its infection capability, making use of insect cellular chaperones for enhancing Cry toxicity and for lowering the evolution of insect resistance to these toxins.